Ripensare le visite didattiche dopo la pandemia - Giuseppe De Simone; Michele Domenico Todino (Firenze University Press, 2022)
The Covid-19 pandemic has shown us that every educational institution has a duty to value more than outdoor activities and artistic and cultural heritage. In fact, at times of lock-down they have been missed by students and teachers alike. However, it is risk management that holds teachers back from implementing non-indoor activities (and always staying inside the school walls). This paper proposes an examination of these issues, the purpose of which is to promote a culture of heritage capitalization that has the school as one of its most active promoters.